Hello, can someone please show me the steps involved in solving dy/dx for this function:
x + xy = 3.
My attempt is:
1 + y(dy/dx) + x = 0
=
dy/dx = (-1-x) / y
Thanks kindly.
Nearly.
Using the product rule , we get:
I leave the , and differentiate the with respect to . I then leave the and differentiate the with respect to . I have to use the chain rule here:
Notice how the 's would "cancel"? This is an application of the chain rule. I am now differentiating with respect to to give , leaving:
Take it from here.